2022
DOI: 10.1590/1980-220x-reeusp-2021-0553en
|View full text |Cite
|
Sign up to set email alerts
|

Leadership in Nursing and Health Care in the Light of Complexity Thinking

Abstract: This study aims to perform a critical-reflective analysis of leadership in nursing and health in the light of complexity thinking. This is a theoretical-reflexive essay based on the framework of complexity thinking. A parallel is conceived between traditional Cartesian leadership, outlined from a defined linear hierarchical structure, and leadership from a systemic-complex perspective. A schematic structure is demonstrated between the pyramidal conception and systemic-complex leadership, leading to circularity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
0
1
0
4
Order By: Relevance
“…Studies have shown that digitalization and technological innovation need to go hand in hand with leadership. Developing leadership skills in the digital age, good practices for leading and conducting virtual teams are currently the main findings in the different areas of knowledge ( 26 , 27 ) . In the development of a digital/technological culture, in which all the members of a team feel they are protagonists and co-responsible, leaders are drivers and key players.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that digitalization and technological innovation need to go hand in hand with leadership. Developing leadership skills in the digital age, good practices for leading and conducting virtual teams are currently the main findings in the different areas of knowledge ( 26 , 27 ) . In the development of a digital/technological culture, in which all the members of a team feel they are protagonists and co-responsible, leaders are drivers and key players.…”
Section: Discussionmentioning
confidence: 99%
“…Estudos demostraram que a digitalização e a inovação tecnológica precisam caminhar de mãos dadas com a liderança. Desenvolver habilidades de liderança na era digital, boas práticas para liderar e conduzir equipes virtuais são, atualmente, as principais descobertas nas diferentes áreas do conhecimento (26)(27) . No desenvolvimento de uma cultura digital/tecnológica, na qual todos os integrantes de uma equipe se sentem protagonistas e corresponsáveis, os líderes são propulsores e atores-chave.…”
Section: Discussionunclassified
“…Considerando tais características, a liderança é uma competência que pode ser compreendida, na enfermagem, como uma habilidade por meio da qual o enfermeiro-líder influencia sua equipe em prol do alcance de um objetivo comum, atendendo às necessidades de saúde dos pacientes e seus familiares (6) . Deve-se considerar, também, que a liderança integra um processo construtivo que, ao longo dos anos, gera distintos significados e conceitos (7) .…”
Section: Introductionunclassified
“…O cenário da saúde necessita de líderes dispostos a lidar com os imprevistos e as ambiguidades, assim, espera-se que esses atuem com segurança, agilidade e qualidade. Além disso, os enfermeiros precisam estar preparados para exercer a liderança a fim de alcançar melhorias nos níveis da saúde, sendo essencial compor referenciais sistêmicos na educação, na pesquisa e na prática para consolidar a liderança prospectiva e empreendedora (7) .…”
Section: Introductionunclassified
See 1 more Smart Citation